Domestic Violence in Separated Couples in Italian Context: Communalities and Singularities of Women and Men Experiences - Cardinali, Paola; Migliorini, Laura; Giribone, Fiorenza; Bizzi, Fabiola; Cavanna, Donatella (Frontiers in Psychology, 2018)
Relationship breakdown and separation represents a critical aspect in domestic violence. Few studies have investigated domestic violence in separated couples. Moreover, there is a need for a more in depth analysis of gender difference that could enhance the comprehension of the phenomenon. The primary aim of this research was to analyse, through a qualitative approach, which kinds of domestic violence are characteristic or major in separated couples in the Italian context, where this phenomenon has not yet been sufficiently investigated. Participants are 60 separated couples (mean age: M=48; F=44) who attended a Family Mediation Center. A descriptive study was conducted using grounded theory methodology. A brief narrative task was administered to both ex-partners separately. The transcriptions were analysed using NVivo 11 software. From data analysis some themes emerged regarding typology of domestic violence specific of the separation context and shared by both men and women. The analyses of gender differences showed that there is a gender specific experience of domestic violence. Results highlight that women narrate both physical and psychological violence, while men relate only psychological abuse focussed on limiting access to children. We discuss these findings in relation to possible appropriate gender specific intervention and prevention efforts.